Identification and validation of SSR markers for Karnal bunt (Neovossia indica) resistance in wheat (Triticum aestivum) - KUMAR, SANDEEP; CHAWLA, VEENA; YADAV, NEELAM R; SHARMA, INDU; YADAV, PAWAN K; KUMAR, SUNIL; BEHL, R K (The Indian Journal of Agricultural Sciences, 2015)
Present study was carried out to screen 107 recombinant inbred lines (RILs) of cross H567.71 (resistant) × WH 542 (susceptible) for Karnal bunt [Neovossia indica (Mitra) Mundkar] resistance and to identify and validate SSR markers associated with Karnal bunt resistance in wheat (Triticum aestivum L.). There was significant variation among the recombinant inbred lines for percentage and coefficient of infection to Karnal bunt. Most of the RILs (85) and (72) showed up to 5% infection during the year 2010 and 2011 and thus were resistant. The range of percentage of infection (PI) in the susceptible RILs was 5.19 to 22.93 and 5.38 to 36.46 in the year 2010 and 2011 respectively, whereas coefficient of infection on RILs ranged from 0 to 8.28 and 0 to 14.45 in the year 2010 and 2011 respectively. A total of 70 SSR markers were used to screen parental genotypes out of these 42 were polymorphic. Total of 88 alleles were detected, number of alleles per locus ranged from 2-3 with an average of 2.09 alleles per locus. Genetic similarity analysis showed that parental genotypes were quite distinct from each other. The cluster analysis led to distribution of parents and their RILs in to two groups. Major cluster I, included resistant parent H 567.71 with resistant lines and major cluster II had susceptible parent WH 542 and susceptible lines. The three primers (Xgwm 637, Xgwm 337 and Xgwm 538) which were already reported to be associated with Karnal bunt resistance also showed association with Karnal bunt resistance in population under study. A new marker (Xgwm 6) located at 1.6 cM from Xgwm 538 (on chromosome 4B) was identified to be associated with Karnal bunt resistance. These four markers were further used to screen on whole population and results were confirmed. Hence, these markers may be used for marker assisted selection for Karnal bunt resistance in early segregating generations.